EDUKASI GIZI PEDOMAN GIZI SEIMBANG DAN ISI PIRINGKU PADA ANAK SEKOLAH DASAR NEGERI 06 BATANG ANAI KABUPATEN PADANG PARIAMAN - Hafifatul Auliya Rahmy; Nurul Prativa; Rahmania Andrianus; Mesa Putri Shalma (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Their knowledge of nutrition is one of the causes of indirect malnutrition. Increased knowledge through education nutrition to prevent malnutrition and improve a person's behaviour to consume food according to school-age children's nutrition. Knowledge is one of the factors that influence the attitudes and conduct of one. One promotion of health aimed at increasing knowledge to change someone's attitude is nutrition education about nutrition. SDN 06 Batang Anai from many schools is one of the schools that had received the nutrition assistance programs called "Pojok Gizi." Based on the corner nutrition results by working with the JAPFA foundation obtained in functional literacy, students about balanced nutrition are still low. Students who have functional literacy nutrition good only 16 %. This community service aims to provide balanced nutrition and fill my plate education to SDN 06 Batang Anai students. Activities are conducted with the methods lectures with uses the media slide share. Before and after education data collection was done, evaluation students use the knowledge consisting of 10 questions. The outcome of the activities shows the average score increased since knowledge education students. Data analysis uses statistical tests or dependent t-test. The sample shows differences in the welfare between their knowledge about nutrition education students before and after a p-value 0,02. A conclusion that can be taken is to increase their knowledge about nutrition education students about nutrition and fill My plates. In turn, behaviour and this expected the consumption balanced nutrition and application of my plate right.